THE SUSTAINABILITY REPORT MODERATES THE FACTORS THAT AFFECT THE COMPANY'S VALUE IN FOOD AND BEVERAGE COMPANIES IN ASEAN - Sri Mulyati; Trisandi Eka Putri; Dinda Nursely; Bambang Sugiharto; Asep Kurniawan (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to find out how the influence of Profitability, Liquidity, Company Size on Company Value with Sustainability Report as a moderation variable. The indicators in this study are Profitability measured using Return On Asset, Liquidity using Current Ratio, Company Size using Total Asset LN, Company Value using Price to Book Value, and Sustainability Report using SDRI. The population used in this study is food and beverage subsector companies registered in ASEAN for the 2021-2023 period. This research is a quantitative type of research with a sample selection method using purposive sampling techniques, and a research sample of 267 data was obtained. The analysis methods used in this study are panel data regression analysis and Moderated Regression Analysis (MRA). The results of the study show that the variables Profitability and Liquidity have a positive effect on Company Value, while Company Size has no effect on Company Value. In addition, the Sustainability Report is able to moderate Profitability and Liquidity to Company Value but is unable to moderate Company Size to Company Value.